Developments a Three-Tier Multiple-Choice Diagnostic Instrument to Identify Students’ Misconceptions About Changes in the Shape of Object - Rifa Setiani Z; Akhmad Nugraha; Agnestasia Ramadhani Putri (Universitas Pendidikan Indonesia (UPI), 2023)
The fifth-grade elementary school students' daily test results for questions about how objects' shapes change fall short of the required minimum level of completion. Therefore, it is necessary to identify what makes these results so bad.Therefore, a diagnostic test instrument needs to be developed in an effort to detect the causes of low test scores below the minimum completeness criteria obtained by students in material about changes in the shape of objects. The development carried out was by developing a three-tier multiple-choice diagnostic test instrument. This three-tier multiple-choice instrument is very important to develop because it can detect students' understanding of concepts or misunderstandings that occur. This instrument consists of three tiers, including the first tier, which is related to answering questions. The second tier relates to the reasons for choosing answers at the first and third tier regarding the confidence index selected based on the answers and reasons on the first and second tiers. In this regard, the purpose of this study was to produce a three-level multiple-choice diagnostic test product that can be used to identify students' misconceptions about changes in the shape of objects in fifth grade elementary school students. The development method used is design-based research. The results of this development trial were able to identify student misconceptions, with an average percentage of students scientific knowledge in the shape of objects of 12.4%, lack of knowledge of 3.3%, misconceptions of 41%, misconceptions (false positive) of 25.4%, misconceptions (false negative ) of 16%, and lucky guess of 1.9%. In addition, in relation to student responses in the development of this test tool, an average of 80.7% is in the good category. Therefore, it is clear that students can read diagnostic tests well.